MIGRASI MANUSIA DI PESISIR SELATAN PAPUA (Tinjauan Berdasarkan Motif Bumerang Pada Seni Cadas) - Erlin Novita Idje Djami (BALAI ARKEOLOGI PAPUA, 2010)
Boomerang is one of the cultural object or weapon known as the aborigines (indigenous Australian). Its presence in the territory of Papua in the form of motifs in rock art as an illustration of the influence of foreign culture, because the boomerang is not the result of indigenous Papuan culture. Findings boomerang motifs spread over several sites on the southern coast of Papua from the region of Kaimana, Fak-Fak district to the Raja Ampat area. Its existence illustrates the existence of human migration in the past from where and who their supporters. Studies on the motive of a boomerang and the environment became the main target to reveal the influence of human migration and supporters. In addition, studies on the relationship boomerang motifs with other paintings to describe the motives of acculturation.